Selective one pot multicomponent green synthesis of 3-[(aryl)(arylthio)methyl]-1H-indole derivatives utilizing enhanced Lewis acidic sites of Surfactant-assisted ZnO catalyst - Sangale, Vijay B. B.; Jagtap, Rohidas M. M.; Mali, Bhupendra P. P.; Gonnade, Rajesh G. G.; Pardeshi, Satish K. K. (ChemistrySelect, 2023)
Five different ZnO nanocrystallites (ZnO-1 to ZnO-5) were successfully synthesized by a surfactant-assisted hydrothermal technique using various surfactants. All the ZnO nanocrystallites are thoroughly characterized by XRD, IR, UV-DRS spectroscopy and FESEM-EDS analysis. Among the synthesized ZnO nanocrystallites, the CTAB-assisted synthesized ZnO-4 exhibited a fine disc-like morphology with a minimum crystallite size (23 nm). Subsequent to reaction optimization studies, the ZnO-4 is utilized as an efficient catalyst for one pot-three component green synthesis of 3-[(aryl)(arylthio)methyl]-1H-indoles (4a-4p) via. condensation of a variety of indoles, aromatic aldehydes and aromatic thiols at room temperature in water. The single-crystal X-ray structure of 3-[(phenyl)(phenylthio)methyl]-1H-indole (4a) is also been reported (CCDC 2170437). The Lewis acidic property of the catalyst-supported probable mechanism is well proposed subsequent to pyridine-IR studies of the ZnO catalysts. Indeed, CTAB-assisted synthesized ZnO-4 was found to be most effective and selective Lewis acid catalyst for the synthesis of a variety of 3-[(aryl)(arylthio)methyl]-1H-indole derivatives in water at ambient temperature with merits like higher yields, lower reaction time, catalyst recovery and reuse.
Keywords: 3-[(aryl)(arylthio)methyl]-1H-indole; green synthesis; Lewis acidity; Single crystal; ZnO